PENGEMBANGAN E-LKPD BERBASIS MIND MAPPING PADA MATERI SIKLUS HIDUP HEWAN KELAS IV SEKOLAH DASAR - Mei lani; Nyiayu Fahriza Fuadiah; Patricia H.M Lubis (Universitas Muhammadiyah Jakarta, 2023)
This research aims to produce a product in the form of mind mapping-based e-LKPD (electronic- Lembar Kerja Peserta Didik) for grade IV elementary school science learning. There were problems found, namely that teachers did not have innovative teaching resources, still used conventional methods, and there were still students who had not reached the KKM scores that had been set by the school. This researcher and development uses the Research and Development method using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The subjects in this research were class IV students at SDN 136 Palembang. Data collection instruments are in the form of questionnaires and documentation. Data analysis in this research is to obtain validity, practicality and effectiveness. This research and development produced an e-LKPD that was valid to use, with a score of 89% in the